Mechanism of Na+ Insertion in Alkali Vanadates and Its Influence on Battery Performance - Hartung, Steffen (2017)
Sodium-ion batteries may become an alternative to the widespread lithium-ion technology due to cost and kinetic advantages provided that cyclability is improved. For this purpose, the interplay between electrochemical and structural processes is key and is demonstrated in this work for Na2.46V6O16 (NVO) and Li2.55V6O16 employing operando synchrotron X-ray diffraction. When NVO is cycled between 4.0 and 1.6 V, Na-ions reversibly occupy two crystallographic sites, which results in remarkable cyclability. Upon discharge to 1.0 V, however, Na-ions occupy also interstitial sites, inducing irreversible structural change with some loss of crystallinity concomitant with a decrease in capacity. Capacity fading increases with the ionic radius of the alkali ions (K+ > Na+ > Li+), suggesting that smaller ions stabilize the structure. This correlation of structural variation and electrochemical performance suggests a route toward improving cycling stability of a sodium-ion battery. Its essence is a minor Li+-retention in the A2+xV6O16 structure. Even though the majority of Li-ions are replaced by the abundant Na+, the residual Li-ions (≈10%) are sufficient to stabilize the layered structure, diminishing the irreversible structural damage. These results pave the way for further exploitation of the role of small ions in lattice stabilization that increases cycling performance.